Optimalisasi Sumber Daya Alam Tanaman Jagung Menjadi Produk Olahan Nugget Jagung di Desa Wonoayu melalui kegiatan KSMT - Bambang Minto Basuki; Alfi Khoiru Zahroh (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Group 39 from the KSMT Community Service Program (Bachelor Service Candidates) carried out activities in Wonoayu Village, Wajak District, Malang Regency, where the majority of the population worked as farmers and breeders. One of the problems faced by the community in this village is the suboptimal use of corn, because most of the corn is only sold in raw form. To overcome this problem, socialization was given about the development of corn-based MSMEs and training to the community on how to process corn into ready-to-eat products, so that it has a higher selling value and can improve the village economy. The method used in this program is through socialization and training in making corn nuggets to the people of Wonoayu Village. This activity received a positive response, as evidenced by the active participation of the community in the socialization and training. The result of this program is that the community becomes more aware of how to make corn nuggets, and with this program, they can also be more innovative in developing village products to have a higher selling value, so that they can support the economy of the local community.